2005
DOI: 10.1117/1.2137321
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of plasma membrane permeability by laser irradiation of selectively bound nanoparticles

Abstract: Irradiation of nanoabsorbers with pico- and nanosecond laser pulses could result in thermal effects with a spatial confinement of less than 50 nm. Therefore absorbing nanoparticles could be used to create controlled cellular effects. We describe a combination of laser irradiation with nanoparticles, which changes the plasma membrane permeability. We demonstrate that the system enables molecules to penetrate impermeable cell membranes. Laser light at 532 nm is used to irradiate conjugates of colloidal gold, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
107
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…[20][21][22][23][24][25] The gradient for cavitation-induced heating declines sharply from the epicenter, such that direct thermolysis would be limited to targeted cells near the sites of photothermal transduction. [20,23,24] Cavitation is also responsible for transient bubble formation, which can expand by as much as several microns during their microsecond lifespans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25] The gradient for cavitation-induced heating declines sharply from the epicenter, such that direct thermolysis would be limited to targeted cells near the sites of photothermal transduction. [20,23,24] Cavitation is also responsible for transient bubble formation, which can expand by as much as several microns during their microsecond lifespans.…”
mentioning
confidence: 99%
“…[20,23,24] Cavitation is also responsible for transient bubble formation, which can expand by as much as several microns during their microsecond lifespans. [22,33] These microbubbles have been proposed to cause a temporary rupture in cell membranes, [20,21,25] thereby increasing their permeability to EB and other chemical agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Several studies have suggested that while the rate of ion inflow is highest during the first ~10s after laser irradiation, pores can remain open for minutes 1,13 . Assuming that the large Ca 2+ gradient across the membrane cannot be balanced immediately (due to the energy barrier within the pore), a proportion of cells should be expected to show fast influx during the first seconds that would then be slowed down when the first pores close, and continue to approximate the extracellular calcium concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory, Yao and co-workers have demonstrated through experimental results that the plasma membrane can be transiently permeabilized with high efficiency when 30-nm gold nanoparticles are bound to membrane proteins and irradiated with nanosecond pulses [3]. Based on this technique, they have successfully transferred small exogenous molecules into cells.…”
mentioning
confidence: 99%